Anti-inflammatory and protective effects of combined treatment with sitagliptin and melatonin in cardiac ischemia reperfusion injury in obese rats: Involvement of TLR-4/NF-κB pathway - Sun, Hailei; Zhou, Zhengchun; Xuan, Haiyang; Yan, Zhongya (European journal of inflammation, 2021)
Background: Obesity is associated with an augmented risk of myocardial ischemia/reperfusion (I/R) injury. Reduction of I/R injury by effective cardioprotective strategies needs to be investigated in obese subjects. This study aimed to evaluate the combined effects of sitagliptin and melatonin on inflammatory response and TLR4/IκBα/NF-κB signaling following cardiac I/R damage in obese rats. Methods: Sixty-six male Wistar rats (180–200 g) were fed a low fat diet (10% Kcal from lipids) or high fat (45% Kcal from lipids) diets for 12 weeks. High fat-fed (obese) rats experienced 30 min left anterior descending occlusion followed by 24 h reperfusion. Obese rats received sitagliptin (20 mg/kg/day) for 1 month before I/R surgery. Melatonin (10 mg/kg) was injected at early reperfusion. Myocardial infarct size (IS), cTn-I release, pro-inflammatory cytokines, myeloperoxidase (MPO), COX-2 and iNOS, and the protein expressions of TLR4, p-NF-κB/p65, and p-IκBα were evaluated. Results: Monotherapies with sitagliptin-preconditioning or melatonin-postconditioning had no cardioprotective effects in obese rats. However, combined therapy with sitagliptin and melatonin significantly reduced IS, and the release of cTn-I, in comparison to untreated obese rats (p < .01) Moreover, this combination decreased the production of pro-inflammatory cytokines, MPO, COX-2 and iNOS, and the expression of TLR4 and p-NF-κB/p65, while reduced the expression of p-IκBα, in comparison with untreated or monotherapies-received obese rats (p < .01 for all). Conclusion: Combination therapy with sitagliptin and melatonin was a good cardioprotective strategy to modulate the inflammatory responses and TLR4/NF-κB signaling pathway in obese patients with cardiac I/R injury.